Process system and method for manufacturing paper, board, etc.

CN118414460BActive Publication Date: 2026-10-27KEMIRA OY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280083336.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-12-17
Filing Date
2022-12-16
Publication Date
2026-10-27
Estimated Expiration
2042-12-16

AI Technical Summary

Technical Problem

然而,表面施胶需要额外的工艺设备,并且增加了制造工艺中的工艺步骤数量

Benefits of technology

[0062]在生产板时,如衬纸、挂面板、瓦楞板、折叠盒板纸(FBB)、白衬刨花板(WLC)、固体漂白硫酸盐(SBS)板、固体未漂白硫酸盐(SUS)板或液体包装板(LPB),但不限于这些,本发明的处理系统适用于提高板幅的干强度。板的克重可以为至少80g/m2或至少120g/m2,例如在80g/m2至500g/m2或120g/m2至500g/m2的范围内。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004893996140000081
    Figure BDA0004893996140000081
  • Figure BDA0004893996140000091
    Figure BDA0004893996140000091
  • Figure BDA0004893996140000151
    Figure BDA0004893996140000151
Patent Text Reader

Abstract

The invention relates to a treatment system and its use in the manufacture of paper, board, etc. from recycled cellulose fibres. The treatment system comprises as separate components a cationic polymeric component having a charge density of +2.5 meq / g to +6.5 meq / g at pH 7 and an anionic component having a charge density of -3.0 meq / g to -0.03 meq / g, preferably -2.5 meq / g to -0.03 meq / g at pH 7. The anionic component is a mixture comprising i) a cationic starch and ii) carboxymethyl cellulose having a charge density of -4.5 meq / g to -2 meq / g and / or an anionic copolymer obtained by polymerization of acrylamide with 1-60 mol-% of an anionic monomer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a processing system and method for manufacturing paper, board, etc., as described in the preamble of the appended independent claims. Background Technology

[0002] For decades, environmental issues have been a major concern in the manufacturing of paper, board, and other similar products. Attention has focused on the use of raw materials, particularly the efficient use of cellulose fibers and water, which are key components of these processes. For example, the recycling rate of cellulose fiber materials in paper and board manufacturing has steadily increased over the past few decades. This means that cellulose fibers are repeatedly repulped and re-formed into new fiber products before being explicitly discarded from the process cycle. Each time the fibers are repulped, their properties deteriorate: they become shorter and lose some of their flexibility and strength. Simultaneously, the water cycle in the manufacturing process becomes more closed, as the availability of clean influent may be limited, and / or the plant's environmental permits may restrict the permissible amount of effluent water and its COD (chemical oxygen demand) load. The permissible amount of effluent water can even become a limiting factor for water consumption. This means that the plant's freshwater intake is minimized, and the same water used in the process is cleaned and recycled. This, in particular, increases the amount of conductivity and anionicly charged substances in the process water.

[0003] Traditionally, various charged chemicals (such as cationic polymers) have been used to improve the strength properties of produced cellulose fiber webs (e.g., paper, boards, etc.). The function of these strength chemicals is based on electrostatic interactions. Since cellulose fibers typically carry a negative surface charge, the charge of strength chemicals is usually optimized to interact with the negatively charged fibers. However, as mentioned above, repeated repulping today results in fibers carrying less negative charge, meaning the fibers have lost their surface charge. Simultaneously, the amount of competing negatively charged particles and compounds in process water is constantly increasing. This complicates the use of conventional chemical strength additives in the manufacture of paper, boards, etc. It has been observed that some conventional strength agents fail to provide the expected improvements in strength properties, particularly when used in the manufacture of paper or boards from regenerated cellulose fibers.

[0004] WO 2018 / 055239 discloses a method for manufacturing paper, board, etc. In this method, a cationic strength agent is added to a fiber raw material. A dry strength composition is added to the fiber raw material before or after the addition of the cationic strength agent. The dry strength composition comprises a mixture of a synthetic polymer component and a cationic starch component, and has a charge density in the range of -3 to -0.2 meg / g at pH 7.

[0005] One possibility for improving the strength properties of paper or board is surface sizing, especially when strength additives added to the fiber raw material cannot provide the desired strength response. However, surface sizing requires additional processing equipment and increases the number of process steps in the manufacturing process. Therefore, there is a need to find new and effective processing systems, substances, or compositions that can be used to improve the dry strength properties of the produced paper and board by adding them to the fiber raw material. The required processing system should be particularly well-suited to manufacturing processes using recycled fibers. Summary of the Invention

[0006] One object of the present invention is to minimize or even eliminate the disadvantages present in the prior art.

[0007] Another objective is to provide a processing system and method that effectively improves the strength properties of the final paper, board, etc., especially the strength properties of paper, board, etc. containing regenerated cellulose fibers.

[0008] These objectives are achieved by the present invention, which uses the features presented in the characterizing portions of the independent claims. Several preferred embodiments are disclosed in the dependent claims.

[0009] The embodiments mentioned herein relate to all aspects of the invention where applicable, including treatment systems, their uses and methods, even if they are not always mentioned separately.

[0010] According to the present invention, a typical processing system for manufacturing paper, board, etc. from regenerated cellulose fibers comprises the following as independent components:

[0011] - A cationic polymer component with a charge density of +2.5 meq / g to +6.5 meq / g at pH 7, and

[0012] - An anionic component having a charge density of -3.0 meq / g to -0.03 meq / g, preferably -2.5 meq / g to -0.03 meq / g, at pH 7, wherein the anionic component is a mixture comprising the following:

[0013] i) Cationic starch, and

[0014] ii) Carboxymethyl cellulose with a charge density of -4.5 meq / g to -2 meq / g, and / or anionic copolymers obtained by polymerization of acrylamide with 1-60 mol-% anionic monomers.

[0015] According to the present invention, a typical application of the processing system of the present invention is to improve the strength properties, especially SCT strength, of paper, board, etc. containing regenerated cellulose fibers.

[0016] According to the present invention, a typical method for manufacturing paper, board, etc. includes:

[0017] - Obtain fiber raw materials containing regenerated cellulose fibers with a consistency ≥ 2.5% by weight.

[0018] - The cationic polymer component and the anionic component of the processing system according to the present invention are added to the fiber raw material respectively and in this order.

[0019] - Dilute the fiber raw material to a consistency <2.5% by weight, and

[0020] - The fiber raw material is made into a fiber web and the resulting fiber web is dried.

[0021] It has now been surprisingly discovered that treatment systems containing a specific cationic polymer component with a charge density of +2.5 meq / g to +6.5 meq / g provide improved strength effects, particularly in the manufacture of fiber webs (e.g., paper and boards) comprising or composed of regenerated cellulose fibers. This specific cationic polymer component, when used in conjunction with a specific anionic component, is particularly advantageous for the manufacture of multilayer fiber webs (e.g., multilayer boards). The cationic polymer component of the treatment system has a high cationic charge: this allows it to interact with fibers having reduced anionic surface charge, even in environments containing competing anionic charges. It is not desirable to be bound by theory and assume that a portion of the cationic charge might be consumed by competing negatively charged particles and compounds. Nevertheless, cationic sites can still be generated on the fiber surface. These sites then further interact with the anionic component of the treatment system, providing a network of chemical bonds and interactions necessary to create the desired strength effect in the produced paper, boards, etc. Therefore, by using the treatment system according to the invention, even when using fiber raw materials comprising or composed of regenerated fibers with high conductivity and low zeta potential as raw materials, unexpected improvements in the strength properties of the final product can be achieved, especially SCT and burst strength.

[0022] The processing system of this invention refers to a chemical dosing scheme suitable for manufacturing paper, boards, etc. The processing system according to the invention comprises a cationic polymer component and an anionic component as separate components. The cationic polymer component and the anionic component are added to the fiber raw material independently of each other. Preferably, the cationic polymer component is added before the anionic component. In this way, the cationic polymer component can effectively interact with the weak anionic charge of the regenerated cellulose fibers and create cationic anchoring sites for the anionic component of the processing system. Furthermore, when the cationic polymer component is added to the fiber raw material before the anionic component, the risk of unwanted flocculent formation in the fiber raw material is reduced. However, in some embodiments, the reverse addition order may be used, wherein the anionic component is added first, followed by the cationic polymer component.

[0023] The cationic polymer components suitable for use in this invention, measured at pH 7, have a charge density ranging from +2.5 meq / g to +6.5 meq / g, preferably from +3 meq / g to +6 meq / g, and more preferably from +3.5 meq / g to +5.5 meq / g. The charge density of these cationic polymer components is significantly higher than that of conventional cationic strength agents. Surprisingly, this high cationic charge density allows for interaction with anionic components in fiber raw materials comprising or composed of regenerated fibers, providing improved strength properties without negative effects, such as unwanted flocculation.

[0024] According to a preferred embodiment of the invention, the cationic polymer component may comprise a cationic copolymer obtained by polymerizing (meth)acrylamide and a cationic monomer. The cationic polymer component can be obtained using any suitable polymerization method, such as solution polymerization, dispersion polymerization, or emulsion polymerization. The cationic monomer may be selected from: 2-(dimethylamino)ethyl acrylate (ADAM), [2-(acryloyloxy)ethyl]trimethylammonium chloride (ADAM-Cl), 2-(dimethylamino)ethyl acrylate benzyl chloride, 2-(dimethylamino)ethyl acrylate dimethyl sulfate, 2-(dimethylamino)ethyl methacrylate (MADAM), [2-(methacryloyloxy)ethyl]trimethylammonium chloride (MADAM-Cl), 2-dimethyl-aminoethyl methacrylate dimethyl sulfate, [3-(acryloylamino)propyl]trimethylammonium chloride (APTAC), [3-(methacryloylamino)propyl]trimethylammonium chloride (MAPTAC), diallyl dimethylammonium chloride (DADMAC), or any mixture thereof. Preferably, the cationic monomer can be [2-(acryloyloxy)ethyl]trimethylammonium chloride (ADAM-Cl).

[0025] According to one embodiment of the invention, the cationic polymer component may comprise or consist of a cationic copolymer obtained by polymerizing (meth)acrylamide with 23-70 mol-%, preferably 30-70 mol-%, more preferably 30-60 mol-%, of a cationic monomer as defined above. It is even possible that the cationic copolymer may contain anionic charged groups, provided that the total charge of the copolymer is cationic and within a specified range. For example, the cationic copolymer may be obtained by polymerizing (meth)acrylamide with 23-70 mol-%, preferably 30-70 mol-%, more preferably 30-60 mol-%, of a cationic monomer and 1-10 mol-%, preferably 1-5 mol-%, more preferably 1-3 mol-%, of anionic monomer. The anionic monomer may be selected from unsaturated monocarboxylic acids or dicarboxylic acids, such as acrylic acid, maleic acid, fumaric acid, itaconic acid, aconitic acid, succinic acid, citraconic acid, crotonic acid, isocrotonic acid, angelic acid, or tigrinic acid. Preferably, the anionic group is derived from acrylic acid.

[0026] The cationic copolymer obtained by polymerizing (meth)acrylamide with a cationic monomer and optionally an anionic monomer can be linear or crosslinked, for example by using methylenebisacrylamide (MBA).

[0027] According to another preferred embodiment, the cationic polymer component comprises a combination of: (i) a cationic copolymer obtained by polymerization of (meth)acrylamide and at least one of the above-described cationic monomers, and (ii) a cationic auxiliary polymer selected from polyamines (e.g., polyethyleneimine polymers) and homopolymers of cationic monomers, wherein the cationic monomers are, for example, diallyl dimethylammonium chloride (DADMAC), [2-(acryloyloxy)ethyl]trimethylammonium chloride (ADAM-Cl), or [3-(acryloylamino)propyl]trimethylammonium chloride (APTAC). According to a preferred embodiment, the cationic polymer component is a combination of: (i) a cationic copolymer obtained by polymerization of (meth)acrylamide and at least one of the above-described cationic monomers, and (ii) polydiallyl dimethylammonium chloride (polyDADMAC). The cationic polymer component can be obtained by mixing the cationic copolymer and the cationic auxiliary polymer together, or by polymerizing the cationic copolymer in the presence of the cationic auxiliary polymer. The cationic polymer component may contain 25-70 wt%, preferably 30-70 wt%, of a cationic auxiliary polymer selected from homopolymers of polyamines and cationic monomers.

[0028] When the cationic polymer component comprises a combination of a cationic copolymer and a cationic auxiliary polymer as defined above, the cationic copolymer is preferably obtained by polymerization of (meth)acrylamide with 5-50 mol-%, preferably 6-35 mol-%, of at least one cationic monomer as described above. For example, the cationic copolymer is preferably obtained by polymerization of (meth)acrylamide with 20-35 mol-%, preferably 20-30 or 25-35 mol-%, of at least one cationic monomer.

[0029] It has been observed that the presence of cationic auxiliary polymers, particularly polydiallyldimethylammonium chloride, is advantageous in cationic polymer components, especially when the fiber raw material has a high cationic requirement. It is speculated that this cationic auxiliary polymer (preferably polydiallyldimethylammonium chloride) provides interaction with negatively charged substances present in the fiber raw material, while simultaneously enabling the cationic copolymer to effectively interact with the weakly negative surface of the regenerated fiber, thereby creating the network required to improve strength properties.

[0030] According to a preferred embodiment, the cationic polymer component comprises a mixture of polydiallyl dimethylammonium chloride (polyDADMAC) and a cationic copolymer, which is obtained by polymerization of (meth)acrylamide with 5-50 mol-%, preferably 6-35 mol-%, of at least one of the aforementioned cationic monomers. The weight ratio of polyDADMAC to the cationic copolymer in the mixture, based on dry polymer, can be 80:20-20:80, preferably 75:25-25:75, more preferably 67:33-33:67.

[0031] Alternatively, the cationic polymer component may comprise a cationic copolymer obtained by polymerization of (meth)acrylamide and at least 5-50 mol-%, preferably 6-35 mol-%, of at least one cationic monomer as defined above in the presence of polydiallyldimethylammonium chloride (polyDADMAC). The cationic polymer component may contain 25-70 wt-%, preferably 30-70 wt-%, of polydiallyldimethylammonium chloride.

[0032] Polydiallylmethylammonium chloride present in or mixed with cationic copolymers during polymerization can have a weight-average molecular weight in the range of 50,000-1,000,000 g / mol, preferably 60,000-500,000 g / mol, more preferably 75,000-400,000 g / mol. These ranges have been observed to provide highly effective interactions with negatively charged substances in the fiber raw material over a wide pH range.

[0033] According to one embodiment, the cationic polymer component may comprise or consist of a polyethyleneamine polymer. For example, the cationic polymer component may comprise a combination of: a cationic copolymer obtained by polymerizing (meth)acrylamide with at least one of the above-described cationic monomers, and a cationic auxiliary polymer, which is a polyethyleneamine polymer. A suitable polyethyleneamine polymer can be obtained by polymerizing N-vinylformamide and then hydrolyzing a portion of the resulting polyvinylformamide into polyethyleneamine units. Based on the total polymer including polyethyleneamine and polyvinylformamide units, a suitable polyethyleneamine polymer may contain 15-70 mol-%, preferably 15-60 mol-%, more preferably 15-50 mol-%, of polyethyleneamine units.

[0034] As described above, cationic copolymers obtained by polymerization of (meth)acrylamide with at least one cationic monomer can have a weight-average molecular weight in the range of 300,000-5,000,000 g / mol, more preferably 500,000-5,000,000 g / mol, and even more preferably 1,000,000-4,000,000 g / mol. It has been observed that these weight ranges, combined with the amount of cationic monomer, provide the desired interaction with the weakly negative surface of the regenerated fiber and produce the network required to improve strength properties without inducing the formation of large flocs, which are detrimental to strength properties and network formation.

[0035] The weight-average molecular weight (weight-average molecular weight up to 1,000,000 g / mol) used for this purpose was measured using a polyethylene oxide (PEO) calibrated assay via SEC / GPC: the weight-average molecular weight was determined by size exclusion chromatography (SEC) using an Agilent 1100SE chromatograph equipped with an integrated pump, autosampler, and degasser. The eluent used was a buffer solution (0.3125 M CH3COOH + 0.3125 M CH3COONa), the flow rate was 0.5 mL / min, and the temperature was 35 °C. Typical sample concentrations were 2–4 mg / mL, and the injection volume was 50 μL. Ethylene glycol (1 mg / mL) was used as the flow label. The column setup consisted of three columns: one TSKgel PWXL guard column and two TSKgel GMPWXL columns. Detection was performed using an Agilent refractive index detector (T = 35 °C). Molecular weight was determined using routine (column) calibration with the Polymer Standards Service (PES Service) using narrow molecular weight distribution standards for polyethylene oxide / polyethylene glycol.

[0036] Weight-average molecular weights (MMW) above 1,000,000 g / mol are determined by measuring the standard viscosity of the polymer and then estimating the weight-average molecular weight from a correlation curve based on experimental measurements. Generally, the standard viscosity of a polymer indicates the length and / or weight of its polymer chains. The standard viscosity (SV) was measured in 1 M NaCl aqueous solution at a polymer content of 0.1 wt%, using a Brookfield LV viscometer equipped with a UL adapter, at 25°C, with the UL adapter rotor and a rotation speed of 60 rpm. By determining the standard viscosity (SV) and intrinsic viscosity (IV) of the polymer, a correlation curve can be plotted for weight-average molecular weights above 1,000,000 g / mol. A suitable range of 1.1 × 10⁻⁶ ppm was used, with 1 M NaCl suitable for conditions at 25°C and an intrinsic viscosity (IV) suitable for a range of 1.1 × 10⁻⁶ ppm. 6 -1.5×10 7 The Mark-Houwink-Sakurada constant K = 2.57 × 10 g / mol -4 With dl / g and a = 0.67, the weight-average molecular weight (MW) was calculated from the IV results (Dautzenberg et al., Polyelectrolytes. Formation, Characterization and Application, Carl Hanser Verlag, Munich Vienna New York, 1994, pp. 222-223). The weight-average molecular weight obtained by this method is instructive. As a general guideline, the correlation between the standard viscosity, intrinsic viscosity, and weight-average molecular weight of cationic copolymers of (meth)acrylamide can be established, as shown in Table 1.

[0037] Table 1. General correlation between standard viscosity, intrinsic viscosity and weight-average molecular weight of cationic copolymers of (meth)acrylamide.

[0038]

[0039]

[0040] In addition to the cationic polymer component as defined above, the processing system of the present invention also includes an anionic component having a charge density of -3.0 meq / g to -0.03 meq / g, preferably -2.5 meq / g to -0.03 meq / g, at pH 7. This charge density of the anionic component provides effective interaction with the cationic polymer component, enabling an improved strength effect. The formed polymer network has a larger size, which improves the strength properties of the resulting fiber web comprising or composed of regenerated cellulose fibers.

[0041] The anionic component of the treatment system is a mixture comprising i) cationic starch and ii) carboxymethyl cellulose and / or anionic copolymers obtained by polymerizing acrylamide with 1-60 mol-% anionic monomers. Therefore, this anionic component contains both cationic groups derived from cationic starch and anionic groups primarily derived from carboxymethyl cellulose and / or the anionic copolymer. However, when measured at pH 7, the net charge of this anionic component is anionic.

[0042] According to one embodiment of the invention, the anionic component, calculated by dry weight, may comprise 10-90 wt%, preferably 30-70 wt%, more preferably 40-60 wt%, of carboxymethyl cellulose and / or anionic copolymer, and 10-90 wt%, preferably 30-70 wt%, more preferably 40-60 wt%, of cationic starch component. According to a preferred embodiment of the invention, the ratio of carboxymethyl cellulose and / or anionic copolymer to cationic starch component, based on dry weight, is 40:60-60:40. This ratio is chosen so that the anionic component is net anionic at the pH of the fiber raw material.

[0043] The anionic component of the treatment system may comprise or consist of carboxymethyl cellulose, which has a charge density of -4.5 meq / g to -2 meq / g, preferably -4.0 meq / g to -2.5 meq / g, and more preferably -4.0 meq / g to -3.0 meq / g. The weight-average molecular weight (MW) of the carboxymethyl cellulose can be in the range of 250,000-750,000 g / mol, preferably 300,000-600,000 g / mol. The use of carboxymethyl cellulose increases the amount of the bio-based component in the treatment system and helps reduce the amount of non-renewable components. Furthermore, the linear structure and molecular weight of carboxymethyl cellulose as defined above are advantageous for the structure of the anionic component, creating a high physical size for the anionic component together with the cationic starch component.

[0044] The anionic component of the treatment system may comprise or consist of an anionic copolymer obtained by polymerizing acrylamide with 1-60 mol-% of anionic monomers. According to one embodiment, the anionic copolymer of the anionic component can be obtained by polymerizing (meth)acrylamide with at least one anionic monomer selected from unsaturated monocarboxylic or dicarboxylic acids, such as acrylic acid, methacrylic acid, maleic acid, itaconic acid, crotonic acid, isocrotonic acid, and any mixtures thereof or their salts. The anionic copolymer can be obtained by polymerizing (meth)acrylamide with 3-40 mol-%, preferably 5-25 mol-%, more preferably 5-20 mol-%, and sometimes 9-15 mol-%, of anionic monomers.

[0045] The anionic copolymer of the anionic component can be linear or crosslinked. If the anionic copolymer is crosslinked, a suitable crosslinking agent is used during polymerization in an amount of 50-1000 mg / kg monomer, preferably 50-500 mg / kg monomer. Suitable crosslinking agents include, for example, methylenebisacrylamide, ethylene glycol divinyl ether, di(ethylene glycol) divinyl ether, and tri(ethylene glycol) divinyl ether. Methylenebisacrylamide is a preferred crosslinking agent.

[0046] Anionic copolymers of anionic components can be prepared by any suitable polymerization method, such as solution polymerization, dispersion polymerization, emulsion polymerization, or gel polymerization. According to one embodiment, the anionic copolymer can be obtained by solution polymerization, and the weight-average molecular weight (MW) of the anionic copolymer can be in the range of 300,000-1,000,000 g / mol, preferably 400,000-1,000,000 g / mol, more preferably 500,000-900,000 g / mol. According to another embodiment, the anionic copolymer can be obtained by gel polymerization, and the weight-average molecular weight (MW) of the anionic copolymer can be in the range of 2,000,000-10,000,000 g / mol, preferably 2,500,000-8,000,000 g / mol, more preferably 3,000,000-6,000,000 g / mol. Anionic copolymers obtained by gel polymerization are generally obtained in the form of dry polymers, which is advantageous for microbial stability as well as for transportation and storage.

[0047] According to one embodiment, the anionic component comprises carboxymethyl cellulose and anionic copolymer, i.e., the anionic component is a mixture of carboxymethyl cellulose and anionic copolymer.

[0048] The cationic starch present in the mixture forming the anionic component can be cationic undegraded starch. In this document, this refers to starch modified solely by cationization, and which is neither degraded nor cross-linked. The undegraded starch preferably comprises starch units in which at least 70% by weight, preferably at least 80% by weight, more preferably at least 85% by weight, even more preferably at least 90% by weight, and sometimes even more preferably at least 95% by weight, have an average molecular weight (MW) exceeding 20,000,000 g / mol, preferably exceeding 50,000,000 g / mol, more preferably exceeding 100,000,000 g / mol, and sometimes even exceeding 200,000,000 g / mol.

[0049] The cationic starch can be any cationic starch with the desired cationic properties, such as potato, glutinous potato, rice, corn, glutinous corn, wheat, barley, sweet potato, or cassava starch, or any mixture thereof. In some embodiments, the cationic starch has an amylopectin content of >70%, preferably >80%, more preferably >85%, even more preferably >90%, and sometimes even more preferably >95%.

[0050] The degree of substitution of the cationic starch can be 0.025-0.3, preferably 0.03-0.16, and more preferably 0.045-0.1. The degree of substitution is related to the cationicity of the starch. Cationic starches with relatively high cationicity are preferred for use in dry strength compositions because they provide improved dry strength for the final paper or board.

[0051] When mixed with carboxymethyl cellulose and / or anionic copolymers to form an anionic component, the cationic starch is preferably in the form of an aqueous solution, meaning that the starch has been dissolved in water, for example by cooking at a temperature of 60-135°C.

[0052] Before adding the anionic component to the fiber raw material, the individual components of the anionic component can be mixed together, that is, the anionic component can be added to the fiber raw material as a single solution. The components (i.e., carboxymethyl cellulose, anionic copolymer, and cationic starch) are in solution or dispersion form when mixed. Preferably, before adding the anionic component to the fiber raw material, the cationic starch and anionic copolymer and / or carboxymethyl cellulose are allowed to interact with each other to ensure the formation of a multiionic complex.

[0053] The processing system is suitable for improving one or more strength properties of paper, board, etc., wherein the strength properties are particularly selected from SCT (short span compression test), burst strength and CMT (Concora medium test) strength.

[0054] The cationic polymer component and the anionic component of the treatment system are added, respectively, and in this order, to a fiber raw material with a consistency ≥2.5 wt%, preferably ≥3 wt%.

[0055] Fiber raw materials containing or composed of regenerated fibers and having a consistency ≥2.5 wt% may have a cationic requirement ≥300 μeq / l, sometimes even ≥400 μeq / l. This cationic requirement can be, for example, in the range of 300-2500 μeq / l, typically 400-2000 μeq / l. The fiber raw material may further have an electrical conductivity ≥2 or ≥3 mS / cm, preferably ≥4 mS / cm, sometimes even ≥5 mS / cm. According to one embodiment, the electrical conductivity of the fiber raw material can be in the range of 2-20 mS / cm, typically 3-15 mS / cm, sometimes even 4-15 mS / cm. The cationic requirement of the fiber raw material is measured by means of a filtrate obtained by filtering the fiber raw material through black strip filter paper (e.g., from Schleicher & Schuell).

[0056] According to one implementation, paper, board, etc., are produced in an industrial process where the fresh water intake of the process is <5m³. 3 / ton, sometimes even <3m 3 Paper, board, etc. produced per ton (i.e., metric ton). For example, when the freshwater intake of this process is <5m³. 3 At a rate of / ton, the electrical conductivity of the fiber raw material is typically ≥3mS / cm. When the freshwater intake of the process is <3m... 3 The electrical conductivity of fiber raw materials is typically ≥5 mS / cm per ton.

[0057] The zeta potential of the fiber raw material can be from -15mV to -2mV, preferably from -10mV to -4mV.

[0058] The fiber raw material may preferably contain at least 80% by weight, more preferably at least 90% by weight, and even more preferably at least 95% by weight of regenerated cellulose fibers. According to a preferred embodiment, the fiber raw material consists of regenerated cellulose fibers. Therefore, regenerated fibers in the sense of this application preferably do not include brokes.

[0059] The amount of cationic polymer component added to the treatment system is 0.2-1.5 kg / ton of dry material, preferably 0.2-1 kg / ton of dry material.

[0060] The amount of anionic component added can be 0.5-4 kg / ton of dry fiber raw material, preferably 0.5-3.5 kg / ton of dry fiber raw material, and more preferably 0.75-2 kg / ton of dry fiber raw material.

[0061] According to one embodiment of the present invention, the amount of components added to the processing system is such that the zeta potential of the fiber raw material remains negative.

[0062] In the production of boards, such as linerboard, lining board, corrugated board, folding box board (FBB), white linerboard (WLC), solid bleached sulfate (SBS) board, solid unbleached sulfate (SUS) board, or liquid packaging board (LPB), but not limited to these, the processing system of the present invention is suitable for improving the dry strength of the board width. The basis weight of the board can be at least 80 g / m². 2 Or at least 120g / m 2 For example, at 80g / m 2 Up to 500g / m 2 Or 120g / m 2 Up to 500g / m 2 Within the range. Detailed Implementation

[0063] experiment

[0064] Some embodiments of the present invention are disclosed in the following non-limiting examples.

[0065] Example 1

[0066] Example 1 illustrates the effect of a chemical treatment system comprising cationic and anionic polymer components on various strength properties of the produced fiber web. The strength properties tested were short span compressive strength (SCT), burst strength, and crush resistance (Corrugating Medium Test, CMT30), and the measurement methods are shown in Table 2.

[0067] Table 2 shows the measurement characteristics of the produced sheets and the standard methods used.

[0068] Basis weight Mettler Toledo ISO 536 Short Span Compression Test (SCT) Lorentzen & Wettre ISO 9895 Explosive strength Lorentzen & Wettre ISO 2758 Corrugated base paper test (CMT30) Lorentzen & Wettre ISO 7263

[0069] Fiber raw materials are prepared from European recycled board (RCF).

[0070] A sheet was formed using a Rapid Koethen sheet former (RK) with a basis weight of 110 g / m³. 2 The test paper is formatted as follows:

[0071] RCF was wet-processed at 70°C and a consistency of 3 wt% using a Noviprofibre pulper, without prior soaking. The wet-processing began at 500 rpm for 30 seconds, followed by 1000 rpm for 25 minutes. The resulting fiber material was diluted with tap water to a consistency of 0.5 wt%. The pH and conductivity of the diluted fiber material were adjusted to pH 6.8 and conductivity 3.0 mS / cm, respectively.

[0072] All test points included retention aids, 100 g / t cationic polyacrylamide (charge density approximately 1 meq / g, standard viscosity 3.3 mPas), and 400 g / t silica microparticles (Fennosil 2180, Kemira Oyj).

[0073] The anionic component is a mixture of cationic waxy starch (DS 0.07, charge density 0.4 meq / g) and anionic polyacrylamide (weight average molecular weight 500,000 g / mol, charge density -1.5 meq / g). At pH 7, the charge density of the anionic component is -0.6 meq / g.

[0074] At a mixing speed of 1000 rpm, the following chemicals were added to the fiber raw material in a mixing container:

[0075] 1. Cationic polymer component, at -60s;

[0076] 2. Anionic component, at -40s;

[0077] 3. Cationic polyacrylamide (retention aid), within -15s;

[0078] 4. Silica microparticles (retention aid), at -10s.

[0079] After adding the chemicals used, at 0s, the fiber raw material is poured into the RK paper forming machine, and water is drained through a suction line. The formed paper sheet is removed from the line and vacuum dried under constraint at 92°C. Before laboratory testing, the paper sheet is pre-conditioned for 24 hours at 23°C and 50% relative humidity according to standard ISO 187.

[0080] Table 3 defines the cationic polymer components. [2-(acryloyloxy)ethyl]trimethylammonium chloride is used as the cationic monomer in all cationic polyacrylamides.

[0081] Table 3 shows the cationic polymer components used in Example 1.

[0082]

[0083] *Measured at pH 7

[0084] Table 4 shows the dosage of the cationic polymer component. The dosage of the anionic component was 1.4 kg / t in all experiments. All chemical dosages are given in kg of dry chemical per ton of dry RCF fiber raw material.

[0085] Table 4 shows the results of Example 1. It can be seen that all treatment systems according to the invention (where the cationic polymer component has a charge density >2.5 meq / g) improved the SCT index even at low doses (Test 1). At higher doses, significant increases in both the SCT index and the burst index were observed (Test 4). Furthermore, as the charge density of the cationic polymer component increased, the SCT index, burst index, and CMT30 value all showed substantial improvements (Tests 7-9). This was quite unexpected, as no such general improvement was observed for the reference system, where the cationic polymer component had a charge density <2.5 meq / g (Tests 3, 5, 6, 10). Conversely, no improvement in the burst index was observed for the reference system.

[0086] Table 4 shows the results of Example 3.

[0087]

[0088] Although the invention has been described with reference to what appears to be the most practical and preferred embodiments, it should be understood that the invention is not limited to the embodiments described above, but is also intended to cover various modifications and equivalents within the scope of the appended claims.

Claims

1. A processing system for manufacturing paper or board from regenerated cellulose fibers, said processing system comprising the following as individual components: - A cationic polymer component having a charge density of +2.5 meq / g to +6.5 meq / g at pH 7, wherein the cationic polymer component comprises - Cationic copolymers obtained by polymerizing (meth)acrylamide with 30-70 mol-% cationic monomers; or - Polyvinylamine; or - A cationic copolymer obtained by polymerizing (meth)acrylamide with 5-50 mol-% cationic monomers in the presence of polyDADMAC; or - A mixture of polyDADMAC and a cationic copolymer obtained by polymerizing (meth)acrylamide and at least one cationic monomer in a weight ratio of 80:20 to 20:80 based on dry polymer; and - An anionic component having a charge density of -3.0 meq / g to -0.03 meq / g at pH 7, said anionic component being a mixture comprising: i) Cationic starch, and ii) Carboxymethyl cellulose having a charge density of -4.5 meq / g to -2 meq / g, and / or anionic copolymers obtained by polymerization of acrylamide with 1-60 mol-% of anionic monomers.

2. The processing system according to claim 1, characterized in that... The cationic polymer component comprises the cationic copolymer obtained by polymerizing (meth)acrylamide with 30-60 mol-% of cationic monomers.

3. The processing system according to claim 1, characterized in that... The cationic copolymer obtained by polymerizing (meth)acrylamide with a cationic monomer has a weight-average molecular weight in the range of 300,000-5,000,000 g / mol.

4. The processing system according to claim 1, characterized in that... The cationic polymer component comprises a combination of a cationic copolymer and a cationic auxiliary polymer, wherein the cationic copolymer is obtained by polymerization of (meth)acrylamide with at least one cationic monomer, and the cationic auxiliary polymer is selected from homopolymers of polyamines and cationic monomers.

5. The processing system according to claim 4, characterized in that... The cationic auxiliary polymer is a homopolymer of diallyl dimethyl ammonium chloride (DADMAC), [2-(acryloyloxy)ethyl]trimethyl ammonium chloride (ADAM-Cl), or [3-(acryloylamino)propyl]trimethyl ammonium chloride (APTAC).

6. The processing system according to claim 1, characterized in that... The cationic polymer component comprises the cationic copolymer obtained by polymerizing (meth)acrylamide with 6-35 mol-% cationic monomer in the presence of polyDADMAC.

7. The processing system according to claim 1, characterized in that... The mixture of polyDADMAC and the cationic copolymer contains polyDADMAC and the cationic copolymer in a weight ratio of 75:25 to 25:75 based on dry polymer.

8. The processing system according to claim 1, characterized in that... Poly(DADMAC) has a weight-average molecular weight of 50,000-1,000,000 g / mol.

9. The processing system according to claim 1, characterized in that... The carboxymethyl cellulose has a weight-average molecular weight (MW) in the range of 250,000-750,000 g / mol and / or a charge density in the range of -4.0 meq / g to -2.5 meq / g.

10. The processing system according to claim 1, characterized in that... The anionic copolymer is obtained by polymerizing acrylamide with at least one anionic monomer, wherein the anionic monomer is selected from unsaturated monocarboxylic acids or dicarboxylic acids.

11. The processing system according to claim 1, characterized in that... The anionic copolymer is obtained by polymerization of acrylamide with 3-40 mol-% of anionic monomer.

12. The processing system according to claim 1, characterized in that... The anionic copolymer is obtained by solution polymerization and has a weight-average molecular weight (MW) in the range of 300,000-1,000,000 g / mol.

13. The processing system according to claim 1, characterized in that... The anionic copolymer is obtained by gel polymerization and has a weight-average molecular weight (MW) in the range of 2,000,000-10,000,000 g / mol.

14. Use of the processing system according to any one of claims 1-13 for improving the strength properties of paper or board containing regenerated cellulose fibers.

15. A method for manufacturing paper or board in a process, comprising: - Obtain a fiber raw material containing regenerated cellulose fibers and having a consistency of ≥2.5% by weight. - The cationic polymer component and the anionic component of the treatment system according to any one of claims 1-13 are added separately and in this order to the fiber raw material. - Dilute the fiber raw material to a consistency <2.5% by weight, and - The fiber raw material is formed into a fiber web and the formed fiber web is dried.

16. The method according to claim 15, characterized in that... Fiber raw materials with a consistency >2.5 wt% have a cation requirement >300 µeq, a conductivity >3 mS / cm, and / or a zeta potential of -15 mV to -2 mV.

17. The method according to claim 15, characterized in that... The fiber raw material contains at least 80% by weight of recycled fiber.

18. The method according to claim 15, characterized in that... The cationic polymer component is added at a rate of 0.2-15 kg / ton of dry fiber web.

19. The method according to claim 15, characterized in that... The resulting fiber web has a density of at least 80 g / m 2 The weight in grams.

20. The method according to claim 15, characterized in that... The process has <5 m 3 Freshwater intake per ton of paper or board produced.

Citation Information

Patent Citations

  • Dry strength composition, its use and method for making of paper, board or the like

    WO2018055239A1

  • Method for increasing strength properties of paper or board product

    CN110730842A